2010
DOI: 10.4067/s0716-97602010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical root variations in response to water deficit: wild and domesticated common bean (Phaseolus vulgaris L)

Abstract: Anatomical root variations in response to water deficit: wild and domesticated common bean (Phaseolus vulgaris L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…Some traits in wild P. vulgaris accessions have been associated with resistance to water stress. For example, root anatomy changes (low reductions in parenchyma cells and cell division compared with domesticated genotypes) (Peña‐Valdivia et al., 2010) as well as physiological and biochemical changes in root tissue can occur to provide tolerance to dehydration (Sánchez‐Urdaneta et al., 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Some traits in wild P. vulgaris accessions have been associated with resistance to water stress. For example, root anatomy changes (low reductions in parenchyma cells and cell division compared with domesticated genotypes) (Peña‐Valdivia et al., 2010) as well as physiological and biochemical changes in root tissue can occur to provide tolerance to dehydration (Sánchez‐Urdaneta et al., 2003). …”
Section: Discussionmentioning
confidence: 99%
“…The diameter of xylem vessels and transverse root area diminished in the cultivar, but in the wild common bean were not affected [12]. Stem and cortex diameter, vascular tissue thickness and xylem vessel diameter were reduced under drought stress [13][14]. Some of the above root and stem anatomical responses seem to be adaptations that enhance plant survival in hostile environments [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple characteristics of vascular structure have been investigated, such as modifications of the vascular bundle number and area and alteration of xylem/ phloem ratio, which are thought to be involved in the resistance of the plant to environmental stresses [18]. Several studies have shown that xylem and/or phloem vessel diameter was reduced in Ctenanthe setosa and Triticum aestivum plants subjected to drought stress [2][3][4][5][6][7][8][9][10][11][12][13][14]. Thus, xylem with narrow vessels is physiologically better protected against cavitation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought stress epidermis, cortex and xylem were decreased in common bean (Phaseolus vulgaris L.) [37]. Vessel diameters in stressed root were smaller than those in well-watered plants, and vascular tissue area was decreased by low soil moisture [38].…”
Section: Vascular Tissuementioning
confidence: 99%